La inversión extranjera directa en el sector hotelero y su impacto sobre el crecimiento económico de Bogotá (2014)
The present thesis seeks to show through the sector hotels, restaurants, bars and similar, that: direct foreign investment (FDI) in hotels had a positive impact on the growth of the product of Bogotá through the measurement technique of Ivanov and Webster (2007) modified during the 2007-2012 period. In order to carry out this verification, part of the role of FDI in the growth of GDP of the sector and the city, a role that is taken as proper to the relationship established in the Solow model between investment and economic growth , besides highlighting the effects of the arrival of FDI through the externalities that it produces through the analysis of the factors that have driven it in the hotel sector of Bogotá, in such a way that its impact on the economic growth of the city is highlighted. city ​​through the evolution of the growth of the hotels, restaurants, bars and similar sector; It is considered that this investment is the access route that allows Bogotá to join the international tourism networks, as it enhances its competitiveness as a tourist destination and promotes the influx of foreign tourists, who take as a frame of reference the support that They offer international hotel chains when making their choice. So, the importance of this study lies in the realization of an ex post analysis of the impact of FDI on hotels that brought with it the arrival of the international hotel chains Holiday Inn, Ibis, NH Hotels, Marriot, JW Marriot, Hilton and Sonesta to Bogotá by means of the quantification of the contribution of the hotels, restaurants, bars and similar sector in the economic growth of the city. This in order to evaluate if the new IED in hotels was important at the time of positioning Bogota within the international tourism networks, making it more competitive as an international destination and increasing the influx of foreign tourists to the city in the 2007- 2012 The thesis begins with the definition of the sector hotels, restaurants, bars and similar and tourism, describing the link of this sector with tourism development and its importance in economic growth. In the second chapter, we present the theoretical framework used based on the Solow growth model and the importance of FDI in economic growth according to Borensztein; in addition to an analysis of the determinants of the increase of FDI in Colombia and in the hotel sector based on the evolution of the country as an international tourist destination and its improvements in terms of risk and security, among other situations that explain the country's positioning abroad and Bogotá as a preferred destination for foreign tourists arriving in Colombia. The third chapter describes the model to be used, which is a modification of the methodology presented by Ivanov and Webster (2007) focused on measuring the direct effects of tourism on economic growth. Finally, the fourth chapter carries out the analysis of the link between FDI, the increase in the influx of foreign tourists and the quantification of the contribution of the hotels, restaurants, bars and similar sector within the growth of the city's product through of the importance of the new FDI in Bogota hotels in the analyzed period. The thesis concludes that FDI in hotels has been a factor in promoting the growth of tourism in Bogota and has had a positive impact on the economic growth of the city in the period analyzed.